The Effectiveness Of Implementing The Musyarakah Mutanaqisah (MMQ) Contract On The Financing Of Home Ownership Credit Products (KPR) BTN Syariah Makassar Branch - Hamid, Supriadi; Supriani, Nuraisyah; Arsyad, Kamaruddin (Jurnal Ar-Ribh, 2024)
The purpose of this study was to find out how the implementation of the Musyarakah Mutanaqisah (MMQ) contract for financing home ownership credit (KPR) and to analyze the effectiveness of implementing the MMQ contract for financing KPR products at Bank BTN Syariah Makassar Branch. This type of research is a qualitative research with a descriptive approach. The data sources of this research are primary and secondary data . Data collection methods used in this research are observation, interviews, and documentation. The results of this study indicate that the implementation of the MMQ contract in financing KPR products at the Makassar Branch of BTN Syariah bank is that the bank and the customer jointly buy a house object and then agree to rent it out again to gain profit from the rental with a profit sharing ratio, where the customer as the owner as well as the tenant is obliged to pay installments bank principal and lease, the portion of bank ownership will decrease due to gradual purchases and full ownership for the customer of the object at the end of the period. The results of this study also explain that the application of the MMQ contract in financing KPR products of Bank BTN Syariah Makassar is still ineffective because in practice it still creates a conflict with the characteristics of MMQ.